2017
DOI: 10.1186/s13195-016-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic impact of [18F]flutemetamol PET in early-onset dementia

Abstract: BackgroundEarly-onset dementia patients often present with atypical clinical symptoms, hampering an accurate clinical diagnosis. The purpose of the present study was to assess the diagnostic impact of the amyloid-positron emission tomography (PET) imaging agent [18F]flutemetamol in early-onset dementia patients, in terms of change in (confidence in) diagnosis and patient management plan.MethodsThis prospective bi-center study included 211 patients suspected of early-onset dementia who visited a tertiary memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 29 publications
5
118
0
Order By: Relevance
“…2,3,10,17 Noting that changes in these biomarkers can already be identified when cognitive impairment is mild and in the absence of functional disability (so-called prodromal, or mild cognitive impairment -MCI -stage) 11 new diagnostic criteria incorporating biomarkers now allow for a diagnosis of AD before the development of full-blown dementia (Panel 2). 2,10,17,18 Biomarkers can also be used in the full-blown dementia stage for a more accurate aetiologic diagnosis 19,20 , and, potentially, to screen the general population for persons at high risk of entering the symptomatic stages. 18 Biomarker assessment -Absence of medial temporal (mainly hippocampal) atrophy on MRI in typical (memory) presentations makes AD less likely.…”
Section: The Clinical Context: the Diagnosis Of Prodromal Ad Requiresmentioning
confidence: 99%
“…2,3,10,17 Noting that changes in these biomarkers can already be identified when cognitive impairment is mild and in the absence of functional disability (so-called prodromal, or mild cognitive impairment -MCI -stage) 11 new diagnostic criteria incorporating biomarkers now allow for a diagnosis of AD before the development of full-blown dementia (Panel 2). 2,10,17,18 Biomarkers can also be used in the full-blown dementia stage for a more accurate aetiologic diagnosis 19,20 , and, potentially, to screen the general population for persons at high risk of entering the symptomatic stages. 18 Biomarker assessment -Absence of medial temporal (mainly hippocampal) atrophy on MRI in typical (memory) presentations makes AD less likely.…”
Section: The Clinical Context: the Diagnosis Of Prodromal Ad Requiresmentioning
confidence: 99%
“…It is certainly necessary to further investigate this feature and to adapt the AUCs once new evidence on the usefulness or nonusefulness of amyloid imaging in certain scenarios emerges. For instance, Zwan et al (17) reported that patients might benefit from amyloid imaging even if diagnostic confidence does not increase. Further, given a certain likelihood that disease-modifying antiamyloid drugs will be available in the future, AUCs might need to be expanded to cases in which clinical testing reveals typical AD features ("probable AD dementia").…”
Section: Appropriate Use Criteria (Aucs) For Amyloid Imagingmentioning
confidence: 99%
“…Sixteen studies concerning the clinical utility of amyloid PET imaging were found in the literature (17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Supplemental Table 3 summarizes these studies.…”
Section: Clinical Utility Of Amyloid Imagingmentioning
confidence: 99%
“…The development of PET (positron emission tomography) imaging biomarkers that bind to fibrillar β-amyloid (Aβ), including Pittsburgh compound B ( 11 C-PiB) [13], florbetaben ( 18 F) [14], flutemetamol ( 18 F) [15], and florbetapir ( 18 F) [16,17], has made it possible to estimate whether or not a given patient has moderate-to-frequent neuritic amyloid plaques, a required feature for the pathological diagnosis of AD. At least five groups have now begun exploring the potential impact of amyloid PET imaging biomarkers on diagnosis and management in a clinical setting [18,19,20,21,22,23,24,25]. These studies have consistently reported that knowledge of the Aβ status could change the diagnosis in the direction of the scan result, improve physicians' confidence in their diagnosis, and change treatment.…”
Section: Introductionmentioning
confidence: 99%